Static Timing Analysis for Nanometer Designs A Practical Approach - Chadha, Rakesh; Bhasker, J.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Static Timing Analysis for Nanometer Designs: A Practical Approach is a reference for both beginners as well as professionals working in the area of static timing analysis for semiconductors. This book provides a blend of underlying theoretical background and in-depth coverage of timing verification using static timing analysis. The relevant topics such as cell and interconnect modeling, timing calculation, and crosstalk, which can impact the timing of a nanometer design are covered in detail. Timing checks at various process, environment, and interconnect corners, including on-chip variations, are explained in detail. Verification of hierarchal building blocks, full chip, including timing verification of special IO interfaces are covered in detail. Appendices provide complete coverage of SDC, SDF, and SPEF formats. This book is written for professionals working in the area of chip design, timing verification of ASICs and also for graduate students specializing in logic and chip design. Professionals who are beginning to use static timing analysis or are already well-versed in static timing analysis will find this book useful. Static Timing Analysis for Nanometer Designs serves as a reference for a graduate course in chip design and as a text for a course in timing verification for working engineers.
STA Concepts -- Standard Cell Library -- Interconnect Parasitics -- Delay Calculation -- Crosstalk and Noise -- Configuring the STA Environment -- Timing Verification -- Interface Analysis -- Robust Verification.
Keywords: ENGINEERING; COMPUTER AIDED DESIGN; ELECTRONICS; SYSTEMS ENGINEERING; ENGINEERING; COMPUTER-AIDED ENGINEERING (CAD, CAE) AND DESIGN; ELECTRONICS AND MICROELECTRONICS, INSTRUMENTATION; CIRCUITS AND SYSTEMS